DARI DUTCH MANUAL HINGGA RECORDS IN CONTEXTS: PERUBAHAN DAN KESINAMBUNGAN PRINSIP-PRINSIP KEARSIPAN: Array - Raistiwar Pratama (Jurnal Kearsipan, 2018)
Handleiding voor Het Ordenen en Beschrijven van Archieven or simply known as Dutch Manual is the first codified archival standard succeeded in combining provenance and original order as the first twin pillars of archiving. In the nineteenth century the twin originated from France and German were separated. In order to do arrangement and description in archiving, the twin have to be completely understood. As the previous four archival standards (ISAD-G, ISAAR, ISDF, and ISDIAH) of International Council on Archives make the influence of Dutch Manual clear, the same goes for the latest archival standard. This paper describes the continuity and change of the two since they are combined within Dutch Manual, followed by various national standards and currently applied in Records in Contexts, the single and latest archival standard.